DEVELOPMENT OF CULTURAL COMPETENCE OF TEACHERS AS A SOCIAL AND PEDAGOGICAL PROBLEM - SobirovBaxtiyorBoypulatovich (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The article considers the improvement of mechanisms for the development of general cultural competence of teachers in the system of professional development, and provides analytical materials conducted by the author. The article also reflects the problems of situational management in the system of retraining and advanced training of public educators